1994
DOI: 10.1159/000292516
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Birth Weight and Thyroid Function in Preeclampsia-Eclampsia

Abstract: Maternal thyroid function was investigated in 37 preeclamptic and 8 eclamptic patients and 45 normal pregnant women in the third trimester as controls. There were significant correlations between maternal values of total thyroxine (TT4), total triiodothyronine (TT3), thyroxine-binding globulin, free thyroxine index and birth weight of newborns in the patients with preeclampsia-eclampsia, but there was no correlation in the controls. Also, the maternal free thyroxine, free triiodothyronine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 11 publications
3
24
0
2
Order By: Relevance
“…Similar findings were reported by Kaya E et al that serum T 3 , T 4 and TBG values significantly lower and TSH was significantly higher in pregnancy and eclamptic women compared to value of control group. 6 Other studies are also in agreement with our observation showing lower total T 3 and T 4 values and higher TSH value in pre-eclamtic women in third trimester. 2,3,6,7 Modest decrease in thyroid hormones with concomitant increase in TSH level in maternal serum correlated with severity of pre-eclampsia and eclampsia and high levels of endothelin.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similar findings were reported by Kaya E et al that serum T 3 , T 4 and TBG values significantly lower and TSH was significantly higher in pregnancy and eclamptic women compared to value of control group. 6 Other studies are also in agreement with our observation showing lower total T 3 and T 4 values and higher TSH value in pre-eclamtic women in third trimester. 2,3,6,7 Modest decrease in thyroid hormones with concomitant increase in TSH level in maternal serum correlated with severity of pre-eclampsia and eclampsia and high levels of endothelin.…”
Section: Discussionsupporting
confidence: 93%
“…6 Other studies are also in agreement with our observation showing lower total T 3 and T 4 values and higher TSH value in pre-eclamtic women in third trimester. 2,3,6,7 Modest decrease in thyroid hormones with concomitant increase in TSH level in maternal serum correlated with severity of pre-eclampsia and eclampsia and high levels of endothelin. 3 Kumar Ashok et al, observed that more member of preeclamptic women had abnormally high TSH levels at the time of diagnosis when compared to mornotensive women.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hypothyroidism has been listed as one of the causes of high blood pressure , which is one of the factors of preeclampsia [19]. In preeclampsia there is decrease production of estrogen resulting in decrease levels of thyroxine binding globulin and in turn low levels of thyroid hormones [20]. Pre-eclampsia was observed in 20.83% of hypothyroid ladies as compared to 9.1% in ladies with normal TSH levels.This is a significant observation with p-value <.001.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on preeclamptic patients have revealed that 16.7% and 43.7% of subjects were sub-clinical and overt cases of hypothyroidism respectively during pregnancy [6]. Preeclamptic women show high incidence of hypothyroidism that might correlate with the severity of preeclampsia [7,8,9].…”
Section: Introductionmentioning
confidence: 99%